Pengembangan Sistem Informasi Penjualan Furnitur Pada CV UD Hidayah - Alfurizma Ramadhani; Adam Hendra Brata; Eriq Muh. Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In a furniture business, marketing is very important, with a good marketing, writer hope it can reach many buyers, so the furnitur sales will be more and the income will rise up higher. Also communication between seller and buyer. The better and tidier of communication, writer hopes there is will be no miss communication in the furniture business process. And also with convenience in selling and buying furniture process. The more convenience in buying and selling furniture, the writer hopes the buyer will be satisfied and gives a good impression, so the other buyer will be intererested and the seller's income rises up higher. With that it will be needed an information system with a form of website to fulfill the requirements of CV UD Hidayah Banyuwangi on solving their problem now. This information system is made for hope to CV UD Hidayah's marketing becomes better, communication is recorded tidily, also convenience in a process of buying and selling furniture for CV UD Hidayah it self. In the process of buying and selling the furniture, the system uses create read update delete method, but on the special order process, the system uses a classification method, named rule base. Rule base method is a method that uses IF-Route to classify result based on buyer's input. In this experiment this time, the result of test is measured with accuracion testing. Took 10 samples of IF-Route and test the accuracion rate from the information system. And the result from the testing of 10 kind of samples are already correct, so the accuracion testing for information system of furnitur sales is already suitable with user's need.